Environmentally friendly green approach for the fabrication of silver oxide nanoparticles: Characterization and diverse biomedical applications. Issue 11 (14th July 2020) - Abbasi, Banzeer Ahsan; Iqbal, Javed; Nasir, Jamal Abdul; Zahra, Syeda Anber; Shahbaz, Amir; Uddin, Siraj; Hameed, Safia; Gul, Farhat; Kanwal, Sobia; Mahmood, Tariq
Abstract: In the present study, green silver nanoparticles (Ag2 ONPs) were prepared from aqueous and ethanolic leaves extract of Rhamnus virgata in a facile, green, cost‐effective, and eco‐friendly way. The color changes from light brown to brownish black determined the synthesis of Ag2 ONPs(Aq) and Ag2 ONPs(Et) . The phytofabrication of Ag2 ONPs was confirmed using various spectroscopic and microscopic techniques: energy‐dispersive X‐ray spectroscopy, dynamic light scattering, ultraviolet–visible spectroscopy, Fourier‐transform infrared, X‐ray powder diffraction, Raman, scanning electron microscopy, and transmission electron microscopy. Detailed in vitro biological activities determined significant biopotentials for Ag2 ONPs. The Ag2 ONPs(Aq) and Ag2 ONPs(Et) were investigated for anticancer potential against HUH‐7 (IC50 : 9.075 μg/ml for Ag2 O(Aq) and 25.66 μg/ml for Ag2 O(Et) ) and HepG2 (IC50 : 25.18 μg/ml for Ag2 O(Aq) and IC50 : 27.74 μg/ml for Ag2 O(Aq) ) cell lines. Concentration‐dependent cytotoxicity was performed against brine‐shrimps (IC50 : 36.04 μg/ml for Ag2 O(Aq) and 28.82 μg/ml for Ag2 O(Et) ) and Leishmanial parasite (amastigotes and promastigotes). Disc‐diffusion method revealed significant antimicrobial activities. In addition, significant enzyme inhibitory activity and antiradical potentials were studied. The hemocompatible nature of Ag2 ONPs(Aq) and Ag2 ONPs(Et) was revealed using biocompatibility tests. In conclusion, the green Ag2 ONPs(Aq) and Ag2 ONPs(Et) are nontoxic and biocompatible and has shown significant biological activities. We further encourage in vivo studies to ensure biosafety and biocompatibility, so that they can be effectively utilized in nano‐pharmaceutical industries. Research Highlights: Aqueous and ethanolic extracts of Rhamnus virgata was utilized for the synthesis, characterization, and investigation of biopotential of Ag2 ONPs. On the whole, Ag2 ONPs were found to be potential in different bioapplications.